The involvement of cytokinin and nitrogen metabolism in delayed flag leaf senescence in a wheat stay-green mutant, tasg1. (January 2019) - Wang, Wenqiang; Hao, Qunqun; Wang, Wenlong; Li, Qinxue; Chen, Fengjuan; Ni, Fei; Wang, Yong; Fu, Daolin; Wu, Jiajie; Wang, Wei
Highlights: Cytokinin metabolism was involved in delayed flag leaf senescence in a wheat stay-green mutant, tasg1 . N metabolism was involved in delayed flag leaf senescence in a wheat stay-green mutant, tasg1 . The cisZOGT1 gene has an important role in regulating wheat leaf senescence by regulating cytokinin and N metabolism. Abstract: In the present study on a wheat stay-green mutant, tasg1, we found that its delayed senescence at the late filling stage was related to the high cytokinin (CK) and N contents. RNA sequencing suggested that several genes may be responsible for the different senescence processes between wild-type (WT) and tasg1 plants. WT and tasg1 seedlings were treated with NH4 NO3, lovastatin, and 6-benzylaminopurine (BAP), and the results suggested that the feedback of CK with N content regulated the leaf senescence in the tasg1 plants. Furthermore, a knock-out of the candidate gene cisZOGT1 (catalytic O-glucosylation in cis -zeatin) in the wheat mutant pool 'Kronos' exhibited delayed senescence at the late grain filling stage. Overall, our results suggested the cisZOGT1 gene has an important role in regulating wheat leaf senescence by regulating CK and N metabolism. At the same time, CK and N metabolism involved in delayed flag leaf senescence of tasg1 may be by a feedback pattern.